The Effect of Elderly Cognitive Care on the Cognitive Function and Physical Activity of Elderly - Hyan Oktodia Basuki; Joni Haryanto; Tiyas Kusumaningrum (Indonesian Journal of Health Research, 2018)
Background. The process of aging causes various health problems namely the physiological changes of the elderly. The increase in number of elderly is directly proportional to the problems of elderly, including the decreased cognitive function and physical activity. This phenomenon is most commonly found in people over the age of 60 years, but also can attack the age of 40 years. Methods. type of research using quantitative research with quasi experimental pre-posttest design. The Sampling method uses non-probability sampling with purposive sampling. The sample of this research is 62 elderly, divided into treatment and control groups in Puskesmas Jetak Tuban. The questionnaire in this research uses MMSE for cognitive function and Index katz for physical activity. The research was conducted from March to April 2018. Results. the statistical test results uses wilcoxon sign rank test obtained significant values of cognitive function intervention group and physical activity variables, before and after given the intervention, the Elderly Cognitive Care has a calculated value Z= -4.32 and Z = -3.94 with significant value α = 0.00. This result means if value of p value ≤0.05, then the hypothesis is accepted, this means that there is influence of Elderly Cognitive Care to cognitive function and physical activity of elderly in Puskesmas Jetak Tuban. Conclusion. There is an enhancement in cognitive function and physical activity in the elderly, after being given Elderly Cognitive Care. This intervention can be used as management for the elderly against the reduction in cognitive function and physical activity.